Do Public-Private Partnerships Improve the Operational Efficiency of Infrastructure in Mainland China? - Haicheng Xu; Xiao Wei; Bo Wang; Yan Cheng; Yijiao Wang (Advances in Civil Engineering)
Public-private partnerships (PPPs) are widely used to achieve sustainable infrastructure provision. The purpose of this research is to monitor the effects of PPPs in practice. This study calculated the operational efficiency of toll roads in Mainland China and examined the effect of the transformation from government operations to concession on their operational efficiency. The results showed that toll road operations were inefficient in terms of cost savings and that there were significant regional differences in the impact of concession on operational efficiency among three regions. Concession played a positive role in improving the operational efficiency in the eastern region; on the contrary, the influence was significantly negative in the western region. The effect on the central region was not significant. The results indicated that the efficiency advantages of concession were not given full play. The governments of economies in transition should pay more attention to the implementation environment of PPPs to make infrastructure operations more sustainable.